The BMM symmetrising trace conjecture for groups G4, G5, G6, G7, G8. (January 2020) - Boura, Christina; Chavli, Eirini; Chlouveraki, Maria; Karvounis, Konstantinos
Abstract: We prove the BMM symmetrising trace conjecture for the exceptional irreducible complex reflection groups G 4, G 5, G 6, G 7, G 8 using a combination of algorithms programmed in different languages (C++, SAGE, GAP3, Mathematica ). Our proof depends on the choice of a suitable basis for the generic Hecke algebra associated with each group.